As transformações na cidade de Belo Horizonte e a perda dos lugares: a Feira Permanente de Amostras (1936-1964) - Felipe Carneiro Munaier (2014)
This study seeks, through an interdisciplinary approach, relate mainly the concepts of history, memory, identity, heritage and historical time, with the objective of analyze the Permanent Sample Fair as a place that was part of the daily life of Belo Horizonte city and that is, at present, capable of join dispersed memories. The Permanente Sample Fair was created in 1936, from a political project of economic modernization. Be a showcase of the State economy, a place of advertisement, would be its apparent main objective. But in practice, the Permanent Sample Fair has gained new meaning and different uses, making it also a place of recreation. The Permanent Sample Fair was built to replace the old Municipal Market and it worked until the mid-1960s, in Rio Branco Square, where later was built the Governador Israel Pinheiro Bus Terminal. The city of Belo Horizonte is characterized by constants urban transformations that imply the loss of places. It is front this scenario that the research proposes a reflection concerning issues of memory.